2021
DOI: 10.52131/jom.2021.0303.0042
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Perceived Organizational Support, Servant Leadership, Creative Self-Efficacy, and Conscientiousness on Job Boredom Via Job Crafting: A Study on Banking Sector of Pakistan

Abstract: The feeling of job boredom can impede employees’ performances but it can be improved through engaging them in job crafting activities. It is important to understand the concept of job boredom because it can lead to many negative consequences at the work place. The study attempted to investigate the impact of perceived organizational support, servant leadership, creative self-efficacy, and conscientiousness on job boredom through the mediating effect of job crafting. Data has been collected from 450 employees o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…In both instances, the employees’ estimation of the manager's own efforts is a more powerful predictor of supervisory likeability and job satisfaction, but that said, managerial support of employees’ efforts to mitigate boredom also exhibits a significant and meaningful effect. Our work thus corroborates suggestions in prior research that workers’ perception of a supportive organizational climate facilitates their own boredom mitigation (e.g., Marri et al, 2021) and confers positive effects on employee satisfaction (Tsai, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In both instances, the employees’ estimation of the manager's own efforts is a more powerful predictor of supervisory likeability and job satisfaction, but that said, managerial support of employees’ efforts to mitigate boredom also exhibits a significant and meaningful effect. Our work thus corroborates suggestions in prior research that workers’ perception of a supportive organizational climate facilitates their own boredom mitigation (e.g., Marri et al, 2021) and confers positive effects on employee satisfaction (Tsai, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…The interrelationships among worker boredom proneness, the enactment of creative and innovative coping and adaptation mechanisms, and the actual communication between managers and workers, remains unclear. While recent research has found that perceived “organizational support” positively facilitates job crafting and creative self-efficacy to reduce job boredom (Marri et al, 2021), the literature has thus far failed to reveal insight into managerial communication—actual responses of managers—specifically directed toward constructive employee efforts to mitigate boredom. Furthermore, despite substantial research recommending managerial awareness and sensitivity to the dysfunctional consequences of boredom—qualitative efforts to highlight the voices of actual workers experiencing these consequences and their perceptions of managerial communicative and behavioral responses to their coping strategies are needed.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation